More Media, More People--On Social & Multimodal Media Intelligence. - Degerstedt, Lars; Snickars, Pelle (Human IT, 2017)
The purpose of this article is to address contemporary challenges facing media intelligence in an altered information landscape. In order to understand the new situation, the article introduces the notion of social and multimodal media intelligence. With cases taken primarily from the Swedish media intelligence sector, we argue that data driven media intelligence today needs to pay increasing attention to new forms of (A.) crowd-oriented and (B.) multimediasaturated information. Media intelligence usually refers to the gathering of publicly available information about an organisation or a company's competitors--using it to gain business advantages. Traditionally such intelligence has implied a set of techniques and tools that transforms numerical or textual data into useful information for business analysis. Today, however, we argue that such techniques need to consider media alterations in both a social and multimodal direction. By presenting some findings from the so called CIBASproject (as a case study), we describe how Swedish organisations and companies rely on social networking structures and individual decision making as a means to increase response and agile creativity. Yet if media intelligence has witnessed a social transition during recent years, the analyses of other media modalities than text also pose a number of technical hurdles. In this article we use fashion analytics as another case in point, taken from a commercial sector where visual big data is presently in vogue.